The Demographics and Economics of Direct Care Staff Highlight Their Vulnerabilities Amidst the COVID-19 Pandemic. Issue 4 (3rd July 2020) - Almeida, Beth; Cohen, Marc A.; Stone, Robyn I.; Weller, Christian E.
ABSTRACT: An estimated 3.5 million direct care staff working in facilities and people's homes play a critical role during the COVID-19 pandemic. They allow vulnerable care recipients to stay at home and they provide necessary help in facilities. Direct care staff, on average, have decades of experience, often have certifications and licenses, and many have at least some college education to help them perform the myriad of responsibilities to properly care for care recipients. Yet, they are at heightened health and financial risks. They often receive low wages, limited benefits, and have few financial resources to fall back on when they get sick themselves and can no longer work. Furthermore, most direct care staff are parents with children in the house and almost one-fourth are single parents. If they fall ill, both they and their families are put into physical and financial risk.